On the Epistemic Value of Eros. The Relationship Between Socrates and Alcibiades - Candiotto, Laura (Peitho. Examina Antiqua, 2017)
Several key lines concerning the relationship between Socrates and Alcibiades, extracted from the Symposium and the Alcibiades 1, are discussed for the purpose of detecting the epistemic value that Plato attributed to eros in his new model of education. As result of this analysis, I argue for the philosophical significance of the relationship between Socrates and Alcibiades as a clear example – even when failed – of the epistemic role of eros in the dialogically extended knowledge.